Congenital absence of a part of the fallopian tube: a case report - Agarwal, Mukta; Sinha, Hemali H.; Anamika, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Congenital malformations of female genital tract are frequently seen in Gynaecological clinics, incidence being upto 5-6% in cases of infertility. Most of these anomalies are related to uterus and vagina, abnormalities related to ovaries and fallopian tubes are of rare occurrence and the exact incidence of these anomalies are not known, only a few incidental case reports are available in literature. Here, we present a rare case report of absent mid- tubal segment of fallopian tube in a patient of infertility.